2016
DOI: 10.1007/s12325-016-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Panobinostat Plus Bortezomib and Dexamethasone in Treating Relapsed or Relapsed and Refractory Multiple Myeloma: A European Perspective

Abstract: Panobinostat is an oral pan-histone deacetylase inhibitor developed by Novartis. Panobinostat acts via epigenetic modification and inhibition of the aggresome pathway. In August 2015, the European Commission authorized panobinostat for use in combination with bortezomib and dexamethasone for the treatment of relapsed or relapsed and refractory multiple myeloma (MM) in patients who have received ≥2 prior regimens including bortezomib and an immunomodulatory drug. In January 2016, the National Institute for Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Despite advances in supportive and systemic therapies, it remains an essentially incurable disease with a high rate of relapse, rapid acquisition of drug resistance, and a median survival of approximately 4 years . Dexamethasone (DEX) is a key front‐line chemotherapeutic for B‐cell malignant MM, however, MM cells often become DEX resistant . Therefore, further investigation of the molecular mechanisms involved in carcinogenesis and progression of MM is essential for developing new effective therapeutic targets of MM.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in supportive and systemic therapies, it remains an essentially incurable disease with a high rate of relapse, rapid acquisition of drug resistance, and a median survival of approximately 4 years . Dexamethasone (DEX) is a key front‐line chemotherapeutic for B‐cell malignant MM, however, MM cells often become DEX resistant . Therefore, further investigation of the molecular mechanisms involved in carcinogenesis and progression of MM is essential for developing new effective therapeutic targets of MM.…”
Section: Introductionmentioning
confidence: 99%
“…Panobinostat is a potent oral pan-deacetylase inhibitor. It affects growth and survival of MM cells through alteration of (1) gene expression through epigenetic modification and (2) protein metabolism by inhibiting protein degradation [168][169][170][171]. The approval of panobinostat for the treatment of MM was based on the results of phase III randomized double-blind clinical trial (PANORAMA 1), which demonstrated improvement in median PFS of 7.8 months for panobinostat, bortezomib and dexamethasone in comparison with placebo, bortezomib and dexamethasone [168][169][170][171].…”
Section: Panobinostatmentioning
confidence: 99%
“…It affects growth and survival of MM cells through alteration of (1) gene expression through epigenetic modification and (2) protein metabolism by inhibiting protein degradation [168][169][170][171]. The approval of panobinostat for the treatment of MM was based on the results of phase III randomized double-blind clinical trial (PANORAMA 1), which demonstrated improvement in median PFS of 7.8 months for panobinostat, bortezomib and dexamethasone in comparison with placebo, bortezomib and dexamethasone [168][169][170][171]. Panobinostat, in combination with bortezomib and dexamethasone, was recently approved in the USA, Europe and Japan for the treatment of patients with MM who had failed at least two prior regimens including bortezomib and an immunomodulatory agent [168][169][170][171].…”
Section: Panobinostatmentioning
confidence: 99%
See 2 more Smart Citations